Livestock Insurance supports women and their households in East Africa - Banerjee, Rupsha R. (Technical Centre for Agricultural and Rural Cooperation, 2019)
Rupsha Banerjee, social scientist at the International Livestock Research Institute explains how the Index-Based Livestock Insurance (IBLI) was created and how it has helped herders and their families in East Africa.